2020
DOI: 10.1177/1745691620917676
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Behavior Is Goal-Driven

Abstract: We address the relation between goal-driven and habitual behaviors. Whereas in recent years the two have been juxtaposed, we suggest that habitual behavior is in fact goal-driven. To support this view, we show that habitual behavior is sensitive to changes in goal properties (reward contingencies), namely goal value and its expectancy of attainment. Whereas adjustment to these properties may be slower for habitual (or overlearned) than for nonhabitual behavior, this is likely due to the routinized (or automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 146 publications
(200 reference statements)
6
83
0
Order By: Relevance
“…Behavioural and neuroscience research have suggested that reward learning reflects the operation of two distinct neuro-cognitive systems: the goal-directed and habit systems (Balleine & O'Doherty, 2010). Recently, this dichotomy has been challenged by authors proposing that, what we thought were habitual responses, are better understood as goal-directed actions (Kruglanski & Szumowska, 2020). This letter is a critical assessment of this hypothesis, which in our opinion can hardly explain the results of recent studies.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Behavioural and neuroscience research have suggested that reward learning reflects the operation of two distinct neuro-cognitive systems: the goal-directed and habit systems (Balleine & O'Doherty, 2010). Recently, this dichotomy has been challenged by authors proposing that, what we thought were habitual responses, are better understood as goal-directed actions (Kruglanski & Szumowska, 2020). This letter is a critical assessment of this hypothesis, which in our opinion can hardly explain the results of recent studies.…”
mentioning
confidence: 85%
“…This outcome insensitivity is thought to be achieved by extensive reward training (Tricomi et al, 2009). As Kruglanski & Szumowska (2020) has recently pointed out, there is not much evidence of outcome-insensitive behaviour in humans (see also, de Wit et al, 2018). There are, however, studies in which highly-trained responses persist despite being at odd with ongoing goals (e.g., Neil et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural and neuroscience research have suggested that reward learning reflects the operation of two distinct neuro-cognitive systems: the goaldirected and habit systems (Balleine & O'Doherty, 2010). Recently, this dichotomy has been challenged by authors proposing that, what we thought were habitual responses, are better understood as goal-directed actions (Kruglanski & Szumowska, 2020). This letter is a critical assessment of this hypothesis, which in our opinion can hardly explain the results of recent studies.…”
mentioning
confidence: 86%
“…This outcome insensitivity is thought to be achieved by extensive reward training (Tricomi et al, 2009). As Kruglanski & Szumowska (2020) has recently pointed out, D. Luque and S. Molinero XXX 112 there is not much evidence of outcome-insensitive behaviour in humans (see also, de Wit et al, 2018). There are, however, studies in which highly-trained responses persist despite being at odd with ongoing goals (e.g., Neil et al, 2011).…”
mentioning
confidence: 99%